Life Satisfaction Dynamics with Quarterly Life Event Data - Johnston, D.W (My University, 2011)
Using life satisfaction responses from Australian panel data we examine the questions of when and to what extent individuals are affected by major positive and negative life events, including changes in financial situation, marital status, death of a close relative, and being the victim of crime. The key advantage of our data is that we are able to identify these events on a quarterly basis rather than on the yearly basis used by previous studies. We find evidence that life events are not randomly distributed, that individuals anticipate major events to a large extent, and that they fully adapt to many events within 12 months. The estimates can be used to calculate monetary values needed to compensate individuals for life events. Using a new valuation methodology that incorporates these dynamic factors produces considerably smaller compensation valuations than those calculated using the standard approach.
Keywords: Life Events; Satisfaction -- Life; Disadvantage, adversity and resilience; Satisfaction; Life Events; Life; Dsiadvantage, adversity and resilience; Adversity and resilience